Buying Behaviour of Generation Z with Reference to Cause-related Marketing - Kozłowski, Wojciech (Krakow Review of Economics and Management/Zeszyty Naukowe Uniwersytetu Ekonomicznego w Krakowie, 2024)
Objective: This paper examines the prosocial behaviour among Polish consumers of Generation Z. The impact of cause-related marketing (CRM) campaigns on the purchase intention of Generation Z is studied within the framework of attribution theory and social identity theory. Research Design & Methods: The research involved 407 individuals who participated in a between-subjects experiment. The experiment had a 2 × 2 × 4 design, with factors including product type (hedonic, utilitarian), donation magnitude (small, large) and cause category (environment, health, human-being, animal-welfare). Nonparametric tests were employed to test hypotheses. Findings: The author finds empirical evidence that Polish Gen Z consumers are willing to buy products linked with social causes. The study further demonstrates the positive effect of consumer personality (attitude toward CRM, attitude toward helping and cause involvement) on CRM participation. The result of this study also shows that there is no direct causal relationship between the product type, cause category and donation size and the purchase intention of Gen Z. Implications / Recommendations: Marketers should develop CRM campaigns linked with causes that are preferred by Gen Z consumers. In relation to marketing communication, successfully convincing them to purchase cause-related products involves a blend of authenticity and transparency, tangible impact of CRM efforts, social media engagement, and collaboration with influencers who align with the cause and the values of Generation Z. It can strengthen their altruistic motivation and favourable attitudes toward socially responsible initiatives. Contribution: Little is known about the prosocial behaviour of Polish Gen Z consumers. This study is intended to reduce this gap. The findings provide an understanding of the importance of consumer-cause identification and attitudes in cause-related marketing campaigns targeting Z consumers.